2003
DOI: 10.1111/1467-9450.t01-1-00315
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported assertiveness in Swedish and Turkish adolescents: A cross‐cultural comparison

Abstract: The present cross-cultural study compared self-reported assertiveness in 652 Swedish and 654 Turkish high school students by using a multi-dimensional measure called the Scale for Interpersonal Behavior (SIB). Four hypotheses were tested in the study. First, the hypothesis that Swedish adolescents would be more assertive than their Turkish counterparts was supported by the data. Second, the expectation that Turkish boys would be more assertive than Turkish girls, while there would be no differences between Swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
1
30

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 40 publications
6
66
1
30
Order By: Relevance
“…This result was in congruent with the study of Shafiq et al (2015) who found no significant statistical differences regarding communication styles and psychological wellbeing among university students. In contrast, Eskin (2003) indicated that there was gender difference in communicating thoughts and dealing with personal restrictions, where females were found to be more capable than males. However, the present study finding demonstrated gender differences in aspects of communication styles and psychological wellbeing among the studied students.…”
Section: Discussionmentioning
confidence: 90%
“…This result was in congruent with the study of Shafiq et al (2015) who found no significant statistical differences regarding communication styles and psychological wellbeing among university students. In contrast, Eskin (2003) indicated that there was gender difference in communicating thoughts and dealing with personal restrictions, where females were found to be more capable than males. However, the present study finding demonstrated gender differences in aspects of communication styles and psychological wellbeing among the studied students.…”
Section: Discussionmentioning
confidence: 90%
“…Akademik ertelemede cinsiyete dayalı gözlenen farklılıkların nedensellik bağlamında tartışılmasında cinsiyet rolleri üzerinde durulmaktadır. Kollektivist bir yapı olarak kabul edilen Türk kültüründe cinsiyet rollerine ilişkin farkındalıklar bireylerin yaşantılarında oldukça baskın bir konumdadır (Eskin, 2003). Erkek öğrenciler öğrenme ortamlarında erkeksi özelliklerini sergileyebilecekleri davranışlar sergileme eğilimindeyken, ayrıca akademik faaliyetleri yerine getirmeyi kadınsı bir faaliyet olarak algılamaktadırlar.…”
Section: Tartişma Ve Sonuçunclassified
“…In a study by Eşkin (2003), where Turkish and Swedish youth were compared in terms of their level of assertiveness, Swedish youngsters were found to be more assertive and confident. In the same study, women and men were compared in both cultures with regards to their level of assertiveness.…”
Section: Introductionmentioning
confidence: 99%